On Work And Citizenship: About A Book By Tiziana Faitini - Michele Nicoletti (Soft Power, 2024)
With the aim of presenting an overview of the history of “professional ethics” in Western societies, Tiziana Faitini ends up offering us a powerful fresco of the forms of self-realisation and social inclusion linked to the sphere of work and professional activities that have developed from ancient Rome to the present day. The study of the theme of “professionalism,” which at first glance seems to indicate nothing more than the commitment to “doing one’s job well,” turns out, in this patient genealogical analysis, to be a treasure trove of information and suggestions on the great themes of ethical-religious vocation, political identity, social inclusion, and the realisation of the individual’s innermost aspirations and desires. Beneath the tip of the iceberg of Max Weber’s investigations on the Beruf and its inextricable intertwining of “vocation” and “profession,” the book Shaping the Profession sheds light on a fascinating web of spiritual, philosophical, political, and juridical texts spanning over two millennia. Orations, sermons, and treatises alternate with constitutional norms, laws, and deontological codes to “shape” the human activity of daily toil or creative genius. From the common heritage of Medieval Latinity and Christianity to the different national traditions (from Italy to England, from France to Germany), the universe of “arts” and “crafts,” or rather of “making art” and “practising a craft,” is investigated through an analysis of the voices of protagonists and performers. Shaping the Profession succeeds